Reflexões sobre o punitivismo da lei "Maria da Penha" com base em pesquisa empírica numa vara de violência doméstica e familiar contra a mulher do Recife - Medeiros, Carolina Salazar L'armée Queiroga de (2015)
The Law no. 11.340/2006, usually known as Maria da Penha s Law, was enforced in Brazil in response to public and media demands for severe criminal answers towards domestic violence against women, in order to restrain and prevent such violence. Therefore, it s positive to state that Maria da Penha Law is inserted in the context of the penal populism phenomenon, characterized by usual governmental devices on creating symbolical laws focused on the optimum utilization of the punitive system in attempt to solve social problems. These recurrences, however, are fairly criticized because the criminal justice is facing an epistemological legitimacy crisis for failing to fulfill its promises of protecting legal goods and preventing criminal behavior. So, this essay was developed, based on critical criminology findings, in order to evaluate the repercussions of Maria da Penha Law punitiveness, as well as to ascertain whether its purposes are being accomplished. Also, the investigation was focused on the effects of criminal justice s intervention on women (victims) and men (offenders). To assess whether the Law s purposes are being met, as well as to explore its punitive effects, an empirical study was carried out in a domestic violence against women s Court in Recife (Northeast Brazil). Data collection was through participant and non-participant observation (ethnography) of trial hearings, as well as through the documentary analysis of sentenced criminal cases. It was found that both victims and offenders are most often black and belong to the lower classes. Moreover, our data suggests that offender imprisonment has increased, inasmuch as all cases involved petty misdemeanor and offenders were invariably sentenced to prison. Also, because domestic conflicts tend to involve family/affectional bonds, and women are usually keen to drop the case but are prevented by law from doing so, they end up revictimized in the criminal justice system. Moreover, conflict s property stealth by the penal system in order to guarantee penal prosecution ends up ignoring woman s wishes and silencing them. Therefore, towards domestic violence against women, penal system works perfectly in its most traditional ways: selects its clients and reproduces violence and pain. Thus, it was verified that, in general, criminal discourse is inappropriate to address domestic and familiar conflicts, since it ignores the conflict s origin, penalizes women victims and, symbolically and selectively, goes after a guilty party to impose a penalty.